Greening of resistance in Arabic poetry: an ecocritical interpretation of selected Arabic poems - Mohsen, Hamoud Yahya; Ruzy Suliza Hashim (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
In varying degrees, Arabic poetry is rich with natural images but they are employed differently by Arab poets. This article analyses some selected Arabic poems through the lens of ecocriticism to explore how the natural environment is always a shaping force of individuals and contribute to the greening of resistance through parts of the biotic community in the Arab world. The premise of this article has its roots in the recent ecocritical arguments on the elastic and permeable boundaries of the field and its applicability as a lens through which to read any literary text. The discussion is focused on some selected Arabic poems which lend themselves well to the ecocritical interpretation and show how the Arab poets such as Mahmoud Darwish, Tawfiq Zayyad, Fadwa Tuqan, and Salem Jubran engage the natural environment in their poems. The analysis of the selected poems, which represent the other Arabic poems of their genre, advocates the ecocritical way of expressing resistance in Arabic poetry to signify the profound presence and engagement of the natural world in exhibiting the human resistance to the occupation of the land. It also reveals that the Arab poets have highlighted the interconnectedness between the human and nonhuman world in their poetry. By incorporating the Arab viewpoints and voices such as the ones we presented in this article, ecocriticism is instrumental in meeting its targeted scope as a multinational, multi vocal, multicultural area of scholarship.